Expanding the Zone of Reflective Capacity: Taking Separate Journeys Together - Ron Tinsley; Kimberly Lebak (Networks: An Online Journal for Teacher Research, 2009)
The Master of Arts in Education program at our college began in 2004 and was designed to help practicing teachers become more effective and insightful teachers through developing both their content and pedagogical knowledge and helping them to incorporate this new knowledge into their daily practices. The program was designed to culminate in a capstone project. Capstone projects have been used in graduate education as a culmination to the learning experience. The capstone course has been found to be instrumental in helping graduate students “connect theory to practice in a meaningful and collaborative way” (Brown & Bensen, 2005, p. 679). The capstone project serves as the conclusion to our master’s degree in the same way as a traditional thesis, and it includes many of the traditional components of a thesis, such as a review of relevant literature, data collection, data analysis, and reflections on the data.